Status and some prospects of the organization of physical education in higher education institutions - V. Banakh; G. Iedynak (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2021)
The data of sources of information on the organization of physical education in higher education institutions are analyzed and generalized. Problems in the system of organization of physical education concerning the normative-legal base, material-technical, theoretical-methodical and staffing are revealed. Today, higher education is being reformed and integration into the world space, higher education institutions have been given autonomy, which provides for independent decision-making on the organization of the educational process. In such conditions, there is a situation when in some educational programs is no educational component of "Physical Education". In some higher education, physical education classes are held only during the first- second year of study. It is proposed to conduct extracurricular classes lasting two hours twice or thrice a week in extracurricular time. One of the directions of improving the system of organization of physical education is the use of a personalized approach based on individual morphofunctional, psychophysiological features, including personal motives and situational factors.